Toughening an epoxy network by the addition of an acrylic triblock copolymer and halloysite nanotubes. (April 2019) - Rodríguez, Exequiel S.; Falchi, Victoria G.; Asaro, Lucía; Zucchi, Ileana A.; Williams, Roberto J.J.
Abstract: A hybrid epoxy composite was synthesized by adding halloysite nanotubes (HNTs) to an epoxy matrix toughened by an acrylic triblock copolymer (MAM). The morphology generated was composed of spherical MAM domains with sizes in the range of hundreds of nanometers and micron-size clusters of HNTs. The addition of HNTs produced an additional toughening effect with respect to the one generated by MAM. The critical stress intensity factor attained a maximum and then decreased due to the presence of defects generated when increasing the concentration of HNTs. An unexpected result was the decrease of the glass transition temperature produced when increasing the concentration of HNTs. This was ascribed to the different partition of starting monomers inside the cavities of nanotubes, generating a stoichiometric imbalance in the formulation. Highlights: An epoxy matrix was toughened by the simultaneous addition of an acrylic triblock copolymer and halloysite nanotubes. An increase in the critical stress intensity factor was achieved. Microcracking, bridging of cracks, pull-out and fracture of nanotubes were the mechanisms associated to the epoxy toughening.